English Proficiency Issue in Education: A Study on Master's Student - Soomro, Lubna Ahmed; Otho, Wakeel Ahmed; Khalid, Maliha (Annals of Human and Social Sciences, 2023)
This study examines the problem of English language proficiency in the classroom and highlights the difficulties students encounter when expressing themselves in the language. It highlights how significantly English language proficiency affects students' entire educational experience. Additionally, university should implement language support programs and resources to ensure that all students have the opportunity to succeed. This will help create a more inclusive and equitable learning environment for all students, regardless of their language background. Additionally, training and professional teachers should provide ongoing support English language learners in the classroom. This study used mixed method and data analysis to examine the impact of English language proficiency on master students' academic performance, and this study suggests that language barriers can have a detrimental impact on academic performance and overall success. Therefore, it is crucial for educators to address these barriers and provide the necessary support to help students thrive.